Numerical simulation of wall shear stress downstream of a headcut. Issue 1 (10th February 2021) - Wei, Hongyan; Bennett, Sean J.; Yu, Minghui; Zhou, Chi; Jiang, Bole; Duan, Wengang
Abstract : Headcut erosion is a very common process occurring at the head of rills, crop furrows and ephemeral gullies. A numerical model of the headcut flow was built to study the wall shear stress characteristics downstream of the scour hole, which is very important in headcut erosion prediction models. The calculated nappe parameters are very close to experimental data and/or equation results. The calculated flow field, velocity centreline of the free jet part and the locations of the maximum velocity in the scour hole are also close to the experimental data. It was found that the upstream flow rate and downstream water level can affect both the maximum value and the distribution of the wall shear stress. Taking into account the affecting factors and referencing the form of the existing relations on the maximum wall shear stress caused by the impinging jet, the relation of the maximum wall shear stress occurring downstream of the headcut is obtained. The wall shear stress distribution can be described by exponential functions. The new prediction equation of the maximum wall shear stress can be used in existing headcut erosion prediction models for calculating equilibrium scour hole depth or scour hole deepening rate.